Totally blind channel estimation for OFDM on fast varying mobile radio channels. - Necker, M.C (IEEE Transactions on wireless communications)
A new blind channel estimation scheme for orthogonal frequency division multiplexing systems is proposed based on the maximum likelihood principle. By avoiding the use of second- and higher-order statistics, a very fast convergence rate is achieved. A novel approach is also proposed for resolving the phase ambiguity of the blind channel estimate without the need for any reference symbols. The approach combines different modulation schemes on adjacent subcarriers, such as 3-phase shift keying (PSK) and quarternary PSK (QPSK), to resolve phase ambiguity. Simulations were performed for mobile radio environments with high Doppler frequencies and short-to-medium delay spreads. The achieved performance is comparable to that of pilot-based channel estimation for the case of QPSK-modulation.